"Dangerous conversations": a case study involving language. Issue 5 (15th June 2015) - Madoc-Jones, Iolo; Jones, Dawn; Parry, Odette; Dubberley, Sarah
Abstract : Purpose: – Drawing on the approach of Bourdieu (1977, 1986), and using language as an exemplar, the purpose of this paper is to engage in a "dangerous conversation" to explore how and why issues of diversity were mobilised, ignored and leveraged in one particular service context. Design/methodology/approach: – Qualitative research exploring the language choices of 25 service users who had been processed through the criminal Justice System in Wales in the last five years. Findings: – The argument is made that in some service contexts, a habitus obtains that renders reflexivity about diversity issues problematic and predicates against the critical reflection necessary to promote anti-oppressive practice. Research limitations/implications: – Small sample size, not generalisable. Practical implications: – The authors intend the paper to encourage greater reflection on instances when diversity issues are raised and to render simplistic any attempt to invalidate claims of discrimination. Social implications: – Encourage dialogue about claims of discrimination and greater reflection by service providers about the legitimacy of such claims. Originality/value: – Anti-oppressive theorising has, for the most part, constructed minority group members as passive victims within hierarchical power relationships. While acknowledging how power is unequally distributed, the paper challenges hierarchical models which designate minority group members as bereft of power.